Pick me girl (2025)
The scopic regime is a key concept in cultural studies and visual theory. This phenomenon defines the way in which contemporary society is shaped by visuality with all those mechanisms and social interactions that occur within it. It is therefore an essential phenomenon for understanding the different worldviews of different cultures around the world. The priority given to what is seen changes the way people thin